2022
DOI: 10.3390/ijerph19169934
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety and Quality of Life among Online Responders in Poland: A Cross-Sectional Study Covering Four Waves of the COVID-19 Pandemic

Abstract: Introduction: The COVID-19 pandemic has affected the mental health of the population. This study aims to assess the prevalence of subjective depressive and anxiety symptoms as well as assess the quality of life in different waves of the COVID-19 pandemic based on an online survey. Methods: The study was conducted based on an original and anonymous questionnaire, consisting of a section assessing sociodemographic status and psychometric tools: Beck Depression Inventory (BDI), Generalised Anxiety Disorder Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Interesting comparison of mental health of Polish people between the first three waves of the pandemic and the fourth wave was made by Babicki et al [20]. As in the presented study, they found that factors that increased anxiety and depression were younger age, female, and reduced earning capacity.…”
Section: Factors Associated With Poor Mental Health Outcomes (Severe ...mentioning
confidence: 50%
See 2 more Smart Citations
“…Interesting comparison of mental health of Polish people between the first three waves of the pandemic and the fourth wave was made by Babicki et al [20]. As in the presented study, they found that factors that increased anxiety and depression were younger age, female, and reduced earning capacity.…”
Section: Factors Associated With Poor Mental Health Outcomes (Severe ...mentioning
confidence: 50%
“…As in the presented study, they found that factors that increased anxiety and depression were younger age, female, and reduced earning capacity. It can be assumed that the difference in the results of the fourth wave of the pandemic can be explained by the citizen's adaptation to the situation and the loosening of restrictions [20].…”
Section: Factors Associated With Poor Mental Health Outcomes (Severe ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are quite similar to those obtained with the Depression Anxiety Stress Scales (DASS-21) in a study conducted in Turkey in March 2020 on 442 participants who were on the front line and caring for patients with COVID-19, which showed that 64.7% of participants had symptoms of depression, 51.6% had anxiety, and 41.2% had stress [44]. Regarding the evolution of depression symptoms during the two years of the COVID-19 pandemic in Poland, a cross-sectional study covering four waves was published in 2022 and showed that the first three waves had more impact compared to the fourth wave [45].…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the importance of assessing people’s psychological condition during the pandemic and the factors associated to their mental health outcomes. However, the majority of studies were conducted during the first waves, while fewer included the fourth wave [ 8 , 11 ], finding significant differences regarding the impact on mental health of the first waves compared to the last ones. Moreover, there is a lack of Italian studies specifically aimed at broadly assessing such aspects among young people.…”
Section: Introductionmentioning
confidence: 99%